NOWE MODELE W DYDAKTYCE KULTURY. POLSKO-NIEMIECKIE MIEJSCA PAMIĘCI JAKO PRZYKŁAD INNOWACYJNEGO NAUCZANIA JĘZYKA NIEMIECKIEGO W KSZTAŁCENIU AKADEMICKIM - Dziura, Tomasz (Neofilolog, 2018)
One of the main aims of uniting Europe is to create a common European culture of remembrance. To achieve this, different transnational projects are carried out, especially in historical sciences, but increasingly also in other disciplines such as pedagogy. This paper shows a new solution in teaching German as a foreign language at an academic level using the didactics of culture. The lesson unit discussed in this paper was developed within a bilateral project New models of didactics of culture. Polish-German realms of memory during a workshop which had been conducted by students of four universities (two Polish and two German), in order to design lessons curriculums. This article discusses how history and foreign language can be taught within an intercultural lesson unit which focuses on area studies.